Protection against alcohol-induced neuronal and cognitive damage by the PPARγ receptor agonist pioglitazone - Cippitelli, Andrea (Brain Behav Immun, 2017)
Binge alcohol drinking has emerged as a typical phenomenon in young people. This pattern of drinking, repeatedly leading to extremely high blood and brain alcohol levels and intoxication is associated with severe risks of neurodegeneration and cognitive damage. Mechanisms involved in excitotoxicity and neuroinflammation are pivotal elements in alcohol-induced neurotoxicity. Evidence has demonstrated that PPARγ receptor activation shows anti-inflammatory and neuroprotective properties. Here we examine whether treatment with the PPARγ agonist pioglitazone is beneficial in counteracting neurodegeneration, neuroinflammation and cognitive damage produced by binge alcohol intoxication. Adult Wistar rats were subjected to a 4-day binge intoxication procedure, which is commonly used to model excessive alcohol consumption in humans. Across the 4-day period, pioglitazone (0, 30, 60 mg/kg) was administered orally twice daily at 12-h intervals. Degenerative cells were detected by fluoro-jade B (FJ-B) immunostaining in brain regions where expression of pro-inflammatory cytokines was also determined. The effects of pioglitazone on cognitive function were assessed in an operant reversal learning task and the Morris water maze task. Binge alcohol exposure produced selective neuronal degeneration in the hippocampal dentate gyrus and the adjacent entorhinal cortex. Pioglitazone reduced FJ-B positive cells in both regions and prevented alcohol-induced expression of pro-inflammatory cytokines. Pioglitazone also rescued alcohol-impaired reversal learning in the operant task and spatial learning deficits in the Morris water maze. These findings demonstrate that activation of PPARγ protects against neuronal and cognitive degeneration elicited by binge alcohol exposure. The protective effect of PPARγ agonist appears to be linked to inhibition of pro-inflammatory cytokines.